Pendampingan Penyusunan Laporan Keuangan EMKM Menggunakan Cash Basis dan Accrual Basis pada Usaha Mochi - Andi Irfan; Juniar, Retni; Nasaruddin, Fadilah; Olifinda, Shelsy; Dessyka Febria (Journal of Community Sustainability, 2024)
The purpose of this service is to assist in the preparation of financial reports for Mochi Chico MSMEs in accordance with SAK EMKM with a cash basis or accrual basis. The service method is carried out through surveys, workshops, technical guidance, practical implementation, and continuous monitoring with a participatory approach to the preparation of EMKM financial reports. The results of this service are that Mochi business actors are able to prepare financial reports independently using the cash basis and accrual basis methods according to EMKM standards with better accuracy and transparency. The results of the assistance show that the financial report of Mochi Chicho MSMEs presents the financial position in 2023, which precisely from August 23 shows a total asset of IDR 134,080,000 for Profit and Loss in 2023 net profit of IDR 121,080,000 and from the cash flow report it gets IDR 86,365,500 and from the journal of disbursement of fund balances of IDR 82,634,500.